Effect of Slope Aspect on Plant Above‐ and Belowground Functional Traits of Alpine Meadow on the Qinghai‐Tibet Plateau, China. Issue 2 (21st February 2023) - Pan, Yingping; Ren, Liang; Xiang, Xiang; Huo, Jiaxuan; Meng, Dehui; Wang, Yuanyuan; Yu, Cheng; Huang, Yongmei
Abstract: Slope aspects could cause significant differences in microclimate (e.g., radiation and moisture) and edaphic properties (e.g., soil nutrients content) in rugged landscapes. Therefore, understanding the variations of the above‐ and belowground functional traits on hillslope scales and their driving factors are essential for disentangling the plant adaptive strategies to local environmental factors. Based on the measurements of community weighted mean traits of alpine meadow from 15 hillslopes (eight south‐facing and seven north‐facing) in the Qinghai Lake watershed, northeastern Qinghai‐Tibet Plateau, China, we found that the aboveground morphological traits that is, specific leaf area and leaf dry matter content, and belowground stoichiometric traits, that is,  root carbon content (RCC), root nitrogen content (RNC), root phosphorus content (RPC) and RCC: RNC, varied significantly between slope aspects. Hierarchical partitioning indicated that the slope aspect contributed the most to the variations of aboveground morphological and belowground stoichiometric traits, whereas soil properties were the major contributor to aboveground phosphorous‐related traits and belowground morphological traits. Both above‐ and belowground traits displayed a two‐dimensional variation on the hillslope scale. Additionally, the above‐ and belowground traits were weakly coordinated. In general, alpine meadow on the south‐facing slopes tended to adopt the conservative strategy, while acquisitive strategy was preferred by that on the north‐facing slopes. These findings can improve our understanding of spatial variations of functional traits at fine scales, and we highlighted that it is helpful to integrate both above‐ and belowground traits dimensions in disentangling the ecological process and predicting ecosystem function under changing climate. Plain Language Summary: Plant functional traits are a series of measurable characteristics, covering the facet of morphological, physiological, biochemical, etc., and trait‐based methods are powerful tools to disentangle ecological processes. Slope aspects could cause significant microclimate (e.g., radiation and moisture) and edaphic property (e.g., soil nutrients content) differentiation in rugged landscapes. Here, we assessed the changes of above‐ and belowground community weighted mean (CWM) functional traits, and sought to clarify the resource use strategy along the slope aspect gradient. The research was carried out on 15 hillslopes of the Kobresia pygmaea alpine meadow, the largest pastoral alpine ecosystem worldwide stretching 3, 200–5, 200 m a.s.l. on the Qinghai‐Tibetan Plateau, China. We found that traits from various organs responded differently to the slope aspect and soil properties. In addition, the two‐dimensional aboveground, belowground, and whole‐plant traits space were detected at the community level due to multiple environmental stress and functions for various organs in the alpine environment. In general, communities on the south‐facing slope tended to adopt the conservative strategy characterized by higher CWM leaf dry matter content and root carbon content, whilst the communities on the north‐facing slope preferred acquisitive strategy reflected by greater CWM specific leaf area, specific root length, and root nitrogen content. Key Points: Community‐level above‐ and belowground functional traits responded differentially to the slope aspect in the alpine meadow Community‐level above‐ and belowground functional traits of alpine meadow were weakly coordinated on the local scale Contrasting resource‐use strategies were adopted by the alpine meadows on south‐facing and north‐facing slopes